Associations of DDX60L With the Clinical Features and Prognosis of Hepatocellular Carcinoma - Ye, Ziqi; Zhang, Xin; Zhang, Yanfang; Liu, Linqing; Xuan, Zixue; Huang, Ping (Frontiers in Oncology, 2022)
Objective Although the pathogenesis of hepatocellular carcinoma (HCC) is still unclear, hepatitis C virus (HCV) infection is considered a common cause of HCC. It has been reported that DDX60L can inhibit HCV replication, but its role in HCC is still poorly understood. Methods The expression levels of DDX60L in HCC tissues and in tissues adjacent to the tumor and their correlation with the clinicopathological features of patients were analyzed. We also used Kaplan–Meier curves of overall survival (OS) with Cox regression analysis and log-rank test to investigate the prognostic value of DDX60L in HCC. We further performed cell proliferation, Transwell, and wound healing assays to elucidate the role of DDX60L in HCC using the siRNA-DDX60L Hep3B or HCCLM3 cell line. Results Univariate analysis showed that sex, Edmondson grade, microvascular invasion, tumor stage (III–IV/I–II), AFP, and DDX60L expression were strongly associated with the prognosis of HCC patients. The results of multivariate analysis further suggested that DDX60L might be an independent prognostic factor for OS in patients with HCC (Pmoderate/low = 0.015, Phigh/low = 0.011). The low DDX60L expression in HCC patients with no-metastasis, age ≥55 years, tumor size <5 cm, Edmondson grade = I–II, microvascular invasion, no cirrhosis, HBV positivity, tumor stage = III–IV, AFP >20 μg/L, and multiple tumor was associated with poorer prognosis (P <0.05). Moreover, the expression of DDX60L was significantly lower in HCC samples (N = 285) than in the normal tissues adjacent to the tumor (N = 167, P <0.001). There were no HCV-related HCC patients in this study. Additionally, we found that DDX60L knockdown can promote the proliferation of Hep3B cells, migration and invasion ability of Hep3B and HCCLM3 cells. Conclusion We found that the downregulation of DDX60L expression correlated with poor prognosis in patients with HCC, which may be independent of the HCV-related pathway. Furthermore, DDX60L significantly inhibited the proliferation of Hep3B cells, migration and invasion of Hep3B and HCCLM3 cells. Therefore, DDX60L can serve as a prognostic biomarker and therapeutic target for HCC.